Integration of cognitive-motor dual-task training in physical sessions of highly-skilled basketball players - Lucia, S.; Digno, M.; Madinabeita, I.; Di Russo, F. (Journal of Sports Sciences, 2024)
We investigated the effects of a cognitive-motor dual-task training (CMDT) integrated into a physical training circuit. Specific tests on sprint, agility, and cognitive processes associated with anticipatory event-related potential (ERP) components and behavioural performance during a cognitive discrimination response task (DRT) were evaluated before and after the intervention. Thirty skilled basketball players were recruited and divided into an experimental group executing the "physical CMDT" and a control group performing standard physical training. The CMDT session was performed by four athletes simultaneously who executed different circuits. One circuit was the CMDT, implemented with interactive devices thus engaging strong motor control, preparedness, and quick decision-making during task performance. Results on physical performance showed that only the experimental group improved in completion time on sprint (5.83%) and agility (3.55%) tests. At the brain level, we found that in the DRT the motor anticipation increased by over 50%, and the response time became 10% faster. Instead, regarding cognitive preparation, both protocols were equally effective and response accuracy parallelly increased in the post-test. In conclusion, the proposed "physical CMDT" integrated into a group session, can improve sprint and agility and the neural correlate of this effect is the increase of motor preparation in the premotor cortex in only five weeks.